PENGEMBANGAN DESAIN PRODUK BERBASIS BUDAYA UNTUK ALAT PERAGA EDUKATIF (APE) PRODUKSI UMKM DI SURAKARTA - Asmoro Nurhadi Panindias; Etty Ekowati; Putri Sekar Hapsari (Institut Seni Indonesia Surakarta, 2019)
The preparation of excellent quality education and the preparation of a strong successor generation will only be achieved if children from an early age have received appropriate educational stimulation, ie, appropriate stimulation with age and psychological development and specific needs, which take place in an exciting and exciting environment. One of the tools that prioritize education with the game is the APE (Educational Game Tool). UMKM (Micro Small Medium Enterprises) is engaged in the field of APE to help provide educational games for early childhood education institutions and families in need. The objective of this research is to know what kind of APEs are produced in UMKM, to develop the design of culture-based products as the development of the character of early childhood and to increase the production capacity as market demand. Descriptive method to obtain some symptom status information at the time of the research done, the next stage is done planning to solve the problem needs to develop the design of culture-based products, then made the character design of puppet characters. The development stage of educational game-based game design tools. The use of educational game tools produced by UMKM is some kind of puzzle because it is easy and cheap in its manufacture. The use of local culture-based design can form the character of a child who loves the cultural richness of the archipelago, the wayang character of the punakawan character becomes the right choice in puzzle design for early childhood. Product marketing is helped by streamlining promotional media to reach wider consumers.Keywords: APE, budaya, wayang